2014
DOI: 10.3390/biom4030678
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Oxidized Genome Damage and Repair Inhibition by Pro-Oxidant Metals in Neurological Diseases

Abstract: The primary cause(s) of neuronal death in most cases of neurodegenerative diseases, including Alzheimer’s and Parkinson’s disease, are still unknown. However, the association of certain etiological factors, e.g., oxidative stress, protein misfolding/aggregation, redox metal accumulation and various types of damage to the genome, to pathological changes in the affected brain region(s) have been consistently observed. While redox metal toxicity received major attention in the last decade, its potential as a ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 186 publications
0
27
0
Order By: Relevance
“…Seminal work by Graf and associates demonstrated that the availability of only one of the six coordination sites is sufficient to render the iron atom redox active, namely capable of catalyzing the production of hydroxyl radicals by Fenton chemistry (Graf et al, 1984). Increased levels of iron promote neurotoxicity through hydroxyl radical formation, glutathione consumption, protein aggregation, lipid peroxidation, nucleic acid modification, and reduced DNA repair activity (Farina et al, 2013;Jomova et al, 2010;Mitra et al, 2014;Nunez et al, 2004).…”
Section: Redox-active Iron and The Generation Of Rosmentioning
confidence: 99%
“…Seminal work by Graf and associates demonstrated that the availability of only one of the six coordination sites is sufficient to render the iron atom redox active, namely capable of catalyzing the production of hydroxyl radicals by Fenton chemistry (Graf et al, 1984). Increased levels of iron promote neurotoxicity through hydroxyl radical formation, glutathione consumption, protein aggregation, lipid peroxidation, nucleic acid modification, and reduced DNA repair activity (Farina et al, 2013;Jomova et al, 2010;Mitra et al, 2014;Nunez et al, 2004).…”
Section: Redox-active Iron and The Generation Of Rosmentioning
confidence: 99%
“…Several fundamental life functions such as enzymatic catalyzed reactions heavily rely on metal ions [1]. Metal ions are indispensable for cells metabolism in trace; however, in a higher quantity, they could be toxic for human.…”
Section: Introductionmentioning
confidence: 99%
“…It can be released when the structure of these proteins is damaged [18]. Therefore, copper chelators are considered as a promising therapeutic agent to scavenge of free copper ions in the extra-and intracellular spaces [11,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%